Implementation of the institutional repository system in IIUM : issues and challenges - Abdullah, Sarifah (2011)
Purpose - The purpose of this paper is to share with others on the experience of IIUM Library in the implementation of the institutional repository system namely IREP by using the open source system ePrints. Design/methodology/approach – The paper will discuss the issues involved in the implementation of the institutional repository including the choice of software, customization of system, collection, scope and policies, organization and staffing and process of depositing. It also discuss on how this system is used to collect data for research university exercises. Findings – Institutional repository and self- archiving facilitates the university in compiling data for research university exercise. Therefore top management commitment is very essential. Also, it helps highlight the important role libraries play in the organization.